Diagnosis and genetic analysis of polycythemia in children and a novel EPAS1 gene mutationWhat is knownWhat is new? - Hatice Mine Cakmak; Omer Kartal; Ayca Kocaaga; Yasar Bildirici (Pediatrics and Neonatology)
Background: Unlike in adults, there is no consensus on management and diagnosis of polycythemia in children. This study aims to evaluate the diagnosis and verify the algorithm in children with polycythemia. Methods: Seventy-nine children with polycythemia were followed-up in our pediatric hematology-oncology clinic between December 15, 2019, and July 15, 2021. After eliminating secondary causes (hypoxia, pulmonary, cardiac diseases), we checked for genetic mutations, including congenital erythrocytosis gene panel (JAK, EPOR, EPAS1, EGNL1, HBB, HBA, BPGM, and VHL). We also compared parameters for secondary and idiopathic polycythemia groups. Results: Of the 79 children, thirty-five had secondary polycythemia (hypoxia, pulmonary, cardiac diseases), and one was diagnosed with a novel likely pathogenic mutation c.2089C  >  G; p.Pro697Ala in exon 13 of EPAS1 gene. Others (n = 35) had persistent and idiopathic polycythemia. Here, we compared the idiopathic and secondary cases. We found that the ratio of family history of polycythemia (n = 4 (9.5%) vs 0%, respectively) was higher in the second group (p = 0.009). In addition, the mean age (14.7 ± 3.52 vs 13.4 ± 4.67 respectively) (p = 0.042) and the ratio of erythroid hyperplasia in bone marrow [n = 3 (8.6%) vs 0% respectively] (p = 0.003) was higher in the idiopathic polycythemia group, compared to secondary polycythemia patients. Conclusion: Finding the genetic defect in polycythemia is a significant issue. Due to being a rarity in children, the first line JAK mutation analysis should be performed in selected cases. This study is the first description of a Turkish patient with EPAS1 p.Pro697Ala mutation, thereby expanding our knowledge about the clinical features of the disease. However, new investigations are required to confirm its function.